Iranian Women's Experiences of Physical Recovery from Perineal Injuries after Childbirth: A Qualitative Study - Nahid Jahanishoorab; Ali Taghipour; Masomeh Mirteimori; Robab Latifnejad Roudsari (Mashhad University of Medical Sciences, 2021)
Background & aim: The care plan of women with perineal injury during labor does not differ with women without perineal trauma in the health system of Iran, while they are encounter more physical problems after childbirth. The present study was designed to explore the experiences of Iranian postpartum women regarding physical recovery of perineal trauma after child birth.Methods: This qualitative content analysis was conducted on 22 postnatal women with perineal trauma during childbirth delivered in Ommol-banin hospital, Mashhad, Iran, between 20th of April to 25th of December 2017.  Participants were selected purposively until data saturation was achieved. To collect data face-to-face semi-structured interviews were conducted between 10 days to one year after childbirth. Data analysis was carried out using conventional content analysis recommended by Elo and Kyngas (2008) with MAXQDA software.Results: Physical recovery after perineal trauma was conceptualized as a journey toward normalization of body function to reach physical recovery. Two generic categories emerged from the data including (1) experience of illness and (2) physical rehabilitation. In the first phase, participants confronted many complications such as mobile restrictions, sexual disorders and symptoms of illness. Recovery was achieved by alleviating of these disorders and getting better. Improving physical functions helped to restore emotional recovery as well, when participants recaptured pervious sense of self (normalization), and regained their daily activities.Conclusion: Women, especially women with severe perineal trauma, in addition to the routine six-week post-partum care, need longer time of receiving care until completing the natural physical recovery process.